Impact of incomplete revascularization in patients undergoing PCI for unprotected left main stem stenosis. Issue 6 (14th February 2013) - Malkin, Chris J.; Ghobrial, Mina S.A.; Raina, Tushar; Siotia, Anjan; Morton, Allison C.; Gunn, Julian
<x xml:space="preserve">Abstract</x> Introduction Percutaneous revascularization of patients with multivessel and left main stem (LMS) disease may be incomplete and the impact of this is not well reported and may influence outcome. In this study we assessed the role of completeness of revascularization upon outcome after PCI for unprotected left main stem (uLMS) PCI in the "real world." Materials and Method Consecutive patients (n = 353) with uLMS disease were treated by PCI by a single operator with a policy of maximal feasible revascularization between 2000 and 2011. The SYNTAX score was calculated before and after PCI (residual SYNTAX score) to gauge the completeness of revascularization. The endpoints were mortality and repeat revascularization. Results Mean age was 69 ± 11 years, baseline SYNTAX score was 33.4 ± 15, 53% were nonelective, 10% were in cardiogenic shock, and 45% were not surgical candidates. LMS bifurcation was involved in 74% and 2.0 ± 0.9 other vessels were diseased. Complete revascularization was achieved in 49% and was associated with reduced mortality compared with incomplete, at 30 days [5(2.9%) v 23(13%)], 1 year [9(5%) v 34(19%)], and 3 years [14(8%) v 46(26%)]; all P < 0.0001). Median rSYNTAX score was 1(0–11), 1‐year survival for the lowest, middle and highest tertiles of rSYNTAX were 1.7%, 3.1% and 7.3% (P < 0.0001), respectively. In multivariate analysis postprocedure rSYNTAX score independently predicted outcome but preprocedural SYNTAX score did not. Conclusions For unselected patients with uLMS treated by PCI, completeness of revascularization is associated with superior survival. The rSYNTAX score, a novel index of completeness of revascularization, independently predicts survival. Baseline SYNTAX score does not. © 2013 Wiley Periodicals, Inc.